Enhanced photocatalytic activity of ZnO/g-C3N4 composites by regulating stacked thickness of g-C3N4 nanosheets. (February 2020) - Gao, Xingxing; Yang, Binzheng; Yao, Wenqing; Wang, Yajun; Zong, Ruilong; Wang, Jian; Li, Xianchun; Jin, Wenjie; Tao, Dongping
Abstract: A self-assembly method was adopted to synthesize loading architecture of ZnO/g-C3 N4 heterojunction composites by hybridization of g-C3 N4 nanosheets and ZnO nanoparticles utilizing a refluxing method at a low temperature. More importantly, we provided a novel route to regulate the π-π restacking thickness of the g-C3 N4 nanosheets among ZnO/g-C3 N4 composites by the controlling the refluxing time in the ethanol solution, which can optimize the surface hybrid structure, optical response and photocatalytic activity. Among all of samples, ZnO/g-C3 N4 composites with a refluxing 12 h showed the enhancement of photocatalytic activity. The enhanced visible light photocatalytic activity of ZCN-12 composites can be ascribed to the synergistic effects of the construction of hybrid structures, reduction of structural defects of g-C3 N4 nanosheets and suitable π-π restacking g-C3 N4 nanosheets loading thickness. Graphical abstract: Image 1 Highlights: The ZnO/g-C3 N4 composites are synthesized using a refluxing method at a low temperature. The thickness of g-C3 N4 among ZnO/g-C3 N4 composites has been tuned by the refluxing time. ZCN-12 samples with suitable g-C3 N4 thickness showed the excellent photocatalytic activity.